Book Review: The Exploitation of Plant Resources in Ancient Africa. Edited by Marijke van der Veen. Kluwer Academic/Plenum Publishers, New York (ISBN 0 306 46109 9), 1999, 283 pp. - de Moulins, Dominique (African Archaeological Review, 2001)
Reviews the book "The Exploitation of Plant Resources in Ancient Africa," edited by Marijke van der Veen.